ANALISIS HUBUNGAN GAYA KEPEMIMPINAN (LEADERSHIP) DENGAN KINERJA PERAWAT - Abd Kadir; Ryryn Suryaman Prana Putra; Agnes Ratna Saputri; Eny Sendra (Ensiklopedia Research and Community Service Review, 2026)
Nurse performance is influenced by various factors, both individual and organizational. Based on in-depth interviews conducted with five practicing nurses at the Daya Regional General Hospital (RSUD) in Makassar, several issues related to leadership style and nurse performance were identified. The findings indicate that the leadership style of nursing leaders is not yet fully perceived as effective by all practicing nurses. The purpose of this study was to analyze the relationship between leadership style and nurse performance. A cross-sectional design was used in this study. The study was conducted at the Daya Regional General Hospital (RSUD) in Makassar. The study was conducted in April 2025. The study population consisted of all 37 practicing nurses in the inpatient ward, who also became the study sample. The sampling technique used total sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between leadership style (p value: 0.045) and nurse performance. It is recommended that nurses understand the leadership style applied by the head of the ward to produce high-quality performance from practicing nurses at the hospital.         Keywords: Leadership, Performance, Nurses